2018
DOI: 10.1186/s13063-018-2843-9
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of different singly administered high doses of buprenorphine in reducing suicidal ideation in acutely depressed people with co-morbid opiate dependence: a randomized, double-blind, clinical trial

Abstract: BackgroundBuprenorphine is usually administered to treat opioid use disorder and pain syndromes. This research presents the first study regarding the effectiveness of different singly administered high doses of buprenorphine (a partial opioid agonist (of μ-opioid receptors), a potent opioid antagonist (of κ-receptors) and a partial agonist of nociception receptors) in reducing suicidal ideation in acutely depressed people with co-morbid opiate dependence. It follows small studies that suggest that ultra-low-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 33 publications
(16 reference statements)
0
26
0
Order By: Relevance
“…Evidence for BPNʼs direct antisuicidal and mood‐stabilizing effects are just beginning to emerge; this has been shown in the reduction of suicidal ideation in both time‐limited ultra‐low doses of 0.1 to 0.5 mg BPN 13 as well as in single administration of high doses of 32 to 96 mg BPN 14 . Further investigation over this large range of doses and the relative µ‐opioid and κ‐opioid receptor occupancy levels may inform mechanistic hypotheses distinguishing the antisuicidal properties of the compound.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for BPNʼs direct antisuicidal and mood‐stabilizing effects are just beginning to emerge; this has been shown in the reduction of suicidal ideation in both time‐limited ultra‐low doses of 0.1 to 0.5 mg BPN 13 as well as in single administration of high doses of 32 to 96 mg BPN 14 . Further investigation over this large range of doses and the relative µ‐opioid and κ‐opioid receptor occupancy levels may inform mechanistic hypotheses distinguishing the antisuicidal properties of the compound.…”
Section: Discussionmentioning
confidence: 99%
“…Buprenorphine was well tolerated. Similarly, a 3-day study of men with depression and opioid use disorder also demonstrated decreases in suicidal ideation after a large dose of sub-lingual buprenorphine, although this trial was not placebo controlled 329 . Larger studies are needed to replicate the finding that opioids may improve suicidal ideation, and this is an observation that comports with the hypothesis that psychic pain is an important determinant of suicide risk 330 .…”
Section: [H3] Safety Planning Intervention or Crisis Response Planninmentioning
confidence: 97%
“…Suicidal ideation is one of the more severe symptoms that can occur with MDD and TRD. Two studies (Ahmadi, Jahromi, & Ehsaei, 2018; Striebel & Kalapatapu, 2014) reported that suicidal thoughts completely ceased and depression symptoms improved in two patients treated with buprenorphine. However, in one study the patient was opioid dependent and in the other the depression was substance-induced.…”
Section: Buprenorphine and Suicidal Ideationmentioning
confidence: 99%